1999
DOI: 10.1523/jneurosci.19-10-03888.1999
|View full text |Cite
|
Sign up to set email alerts
|

DSD-1-Proteoglycan Is the Mouse Homolog of Phosphacan and Displays Opposing Effects on Neurite Outgrowth Dependent on Neuronal Lineage

Abstract: DSD-1-PG is a chondroitin sulfate proteoglycan (CSPG) expressed by glial cells that can promote neurite outgrowth from rat embryonic mesencephalic (E14) and hippocampal (E18) neurons, an activity that is associated with the CS glycosaminoglycans (GAGs). Further characterization of DSD-1-PG has included sequencing of peptides from the core protein and the cloning of the corresponding cDNA using polyclonal antisera against DSD-1-PG to screen phage expression libraries. On the basis of these studies we have ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
133
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(146 citation statements)
references
References 90 publications
(136 reference statements)
9
133
0
4
Order By: Relevance
“…It has been reported that NSCs treated with an organic solvent to wash out cell surface glycolipids have strong immunoreactivity with anti-Lewis X antibody (41), indicating that this glycotope is carried mainly by glycoproteins and/or proteoglycans rather than glycolipids. To date, phosphacan, CD24, integrin, L1-CAM, Thy-1, LAMP-1, and TNC have been identified as Lewis X-carrying proteins (36,38,(42)(43)(44)(45). Here, we demonstrated that LAMP-1 and TNC are major Lewis X carriers in NSCs (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…It has been reported that NSCs treated with an organic solvent to wash out cell surface glycolipids have strong immunoreactivity with anti-Lewis X antibody (41), indicating that this glycotope is carried mainly by glycoproteins and/or proteoglycans rather than glycolipids. To date, phosphacan, CD24, integrin, L1-CAM, Thy-1, LAMP-1, and TNC have been identified as Lewis X-carrying proteins (36,38,(42)(43)(44)(45). Here, we demonstrated that LAMP-1 and TNC are major Lewis X carriers in NSCs (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…and concentrations of different extracellular matrix and cell adhesion molecules can all affect neuronal behavior (Dou and Levine 1995;Snow et al, 1996;Garwood et al, 1999). For example, regenerating axons grow along NG2-positive blood vessels but stop when they contact other types of NG2-expressing cells (Rezajooi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Maeda et al (20) identified pleiotrophin (PTN), a Hep-binding growthassociated molecule, as a 6B4-PG/phosphacan-binding protein in postnatal day 16 rat brain, and this binding was inhibited by CS-C. 6B4-PG/phosphacan is a major PG in the brain and corresponds to the extracellular region of a receptor-like protein-tyrosine phosphatase, PTP/RPTP␤ (20,21) and recently turned out to be identical with DSD-1-PG (22). MK and PTN constitute a unique family of Hep-binding proteins and share 45% sequence homology at the amino acid level (23,24) in addition to many neuroregulatory activities including promotion of neurite outgrowth (25)(26)(27).…”
mentioning
confidence: 99%